Glucose metabolism impairment as a hallmark of progressive myoclonus epilepsies: a focus on neuronal ceroid lipofuscinoses - Santucci, Lorenzo; Bernardi, Sara; Vivarelli, Rachele; Santorelli, Filippo Maria; Marchese, Maria (Frontiers in Cellular Neuroscience, 2024)
Glucose is the brain’s main fuel source, used in both energy and molecular production. Impaired glucose metabolism is associated with adult and pediatric neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, GLUT1 deficiency syndrome, and the progressive myoclonus epilepsies (PMEs). PMEs, a group of neurological disorders typical of childhood and adolescence, account for 1% of all epileptic diseases in this population worldwide. Diffuse glucose hypometabolism is observed in the brains of patients affected by PMEs like Lafora disease, dentatorubal-pallidoluysian atrophy, Unverricht-Lundborg disease, and myoclonus epilepsy with ragged red fibers. PMEs also include neuronal ceroid lipofuscinoses (NCLs), a subgroup in which lysosomal and autophagy dysfunction leads to progressive loss of vision, brain atrophy, and cognitive decline. We examine the role of impaired glucose metabolism in neurodegenerative diseases, particularly on the NCLs. Our literature review, which includes findings from case reports and animal studies, reveals that glucose hypometabolism is still poorly characterized both in vitro and in vivo in the different NCLs. Better identification of the glucose metabolism pathway impaired in the NCLs may open new avenues for evaluating the therapeutic potential of antidiabetic agents in this population and thus raise the prospect of a therapeutic approach able to delay or even halt disease progression.